Studi Perbandingan Prestasi Belajar Matematika Antara Siswa Yang Diajar Dengan Metode Pemecahan Masalah dan Yang Diajar Dengan Metode Tanya Jawab - Raden Heri Setiawan; Serly Wijayanti (Jurnal Akademik Pendidikan Matematika, 2021)
The problem in this study is whether there is a difference between students who are taught by the problem solving method and those who are taught by the question and answer method of mathematics learning achievement in class VIII SMP Negeri 4 Baubau. The purpose of this study was to determine the difference in achievement between students who were taught by the problem solving method and those taught by the question and answer method of learning achievement in mathematics in class VIII SMP Negeri 4 Baubau. The hypothesis in this study is that there are differences in learning achievement in mathematics between students who are taught by problem solving methods and students who are taught by question and answer methods of Class VIII students of SMP Negeri 4 Baubau. This research is a quasi-experimental research using problem solving methods and questioning methods. responsible for learning Mathematics. The sample was chosen randomly, where class VIII-4 as the experimental class and class VIII-10 as the control class with 24 students each. The data collected were analyzed by descriptive statistics and inferential statistics with t-test. The results showed that there were significant differences between the problem-solving method and the question-and-answer method on mathematics learning achievement on the subject matter of a two-variable linear equation system in class VIII of SMP Negeri 4 Baubau. , or it can be said that learning achievement with problem solving method is better than question and answer method